Helminth parasites in wild rats from peninsular Malaysia oil palm plantation - Aidi Haidzil Johan; Siti Nursheena Mohd Zain; Muhamad Afiq Aziz; Mohd Faris Amjad; Hairul Anuar Md Sahray; Hasmahzaiti Omar (Academia Journal of Biology, 2025)
The presence of wild rats in oil palm plantations not only causes significant losses in crop production but also poses a potential threat to human health through the transmission of zoonotic diseases such as helminthiasis. This study determines the prevalence of helminths among the rat population in an oil palm plantation at Sungai Ara, Johor. By setting 100 metal live traps with baits, a total of 74 individual wild rats consisting of 6 species were successfully caught. Rats were euthanized and necropsied to examine internal organs for the presence of helminths. This study has revealed an overall infection rate of 91.9 %, (n = 68) and recorded several species from two groups of helminths: nematodes (Heterakis spumosa, Nippostrongylus brasiliensis, Syphacia muris, Hepatojarakus malayae, Angiostrongylus spp., Trichuris sp., and Capillaria hepatica) and cestodes (Cyst. Taenia taeniaeformis, Hymenolepis diminuta, and Hymenolepis nana). Among these helminths, several species have been identified as important zoonoses with the potential to infect humans such as taeniasis, hymenolepiasis and capillariasis.